PENERAPAN TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN PADA PERUSAHAAN DI INDONESIA - Erlinda Lusiana; Shinta Permata Sari (Jurnal Akuntansi dan Pajak, 2023)
One of the company's goals is to survive in the long term. For this reason, it is necessary to consider several aspects other than profits, namely the environment and society. Companies carry out economic, social, and environmental activities which are informed to stakeholders through a disclosure, namely a sustainability report to describe better performance per year, especially if the company also implements a good corporate governance mechanism. This research aims to analyze corporate governance's influence on the disclosure of sustainability reports for companies listed on the Asia Sustainability Reporting Rating (ASRRAT) and the Indonesia Stock Exchange (IDX) for 2019-2021. Sustainability reports are measured using the Global Reporting Initiative (GRI) Index. The sample selection used purposive sampling method, with a total sample of 36 companies. Secondary data is used in this study. The data analysis technique uses multiple linear regression. The study's results prove that managerial ownership and the board of directors do not affect sustainability report disclosure. Meanwhile, institutional ownership, audit committee, and board of directors affect sustainability report disclosure.